ANALISIS KINERJA KEUANGAN PT WASKITA KARYA (PERSERO) TBK SEBELUM DAN SELAMA PANDEMI COVID-19 - Rakhmat Hadi Sucipto (Universitas Nusa Cendana, 2022)
The Covid-19 pandemic has had a broad impact on the Indonesian economy, including the construction sector. Many projects were delayed due to the company's funding difficulties. PT Waskita Karya (Persero) Tbk as one of the companies engaged in the construction sector was also affected by the pandemic, indicated by declining financial performance. This study aims to determine the financial performance of PT Waskita Karya before and during the pandemic and to examine the company's financial ratios. The study used descriptive research methods with a quantitative approach. The data comes from internal companies and the Indonesia Stock Exchange. By using the secondary data, the analysis focuses on the current ratio, quick ratio, debt to assets ratio, debt to equity ratio, return on assets, and return on equity. The results showed that several indicators of PT Waskita Karya (Persero) Tbk's financial performance were affected by the Covid-19 pandemic. In terms of liquidity, the current ratio and the quick ratio differ significantly before and during the pandemic. The solvency ratio, both the debt to assets ratio and the debt to equity ratio, were not significantly different before and during the pandemic. In profitability ratios, return on assets and return on equity are both significantly different between before and during the pandemic. Keywords: Covid-19 pandemic, Financial Performance, Financial Ratios